EFFECTIVE TAX RATE DAN FAKTOR -FAKTOR YANG MEMENGARUHI - Gloria; Prima Apriwenni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Effective Tax Rate is the actual tax rate that must be paid by the company compared to the profit generated by the company. The company owners will encourage management to take tax aggressive actions to reduce the tax burden that arises. This study discusses whether company size, leverage and profitability are the dependent variables that can affect the effective tax rate as proxied by ETR as independent variables. The theory that underlies this research is agency theory, which discusses the relationship between owner and management where there is a conflict of interest between the two parties who want to prosper themselves, and political cost theory in which companies minimize costs to increase profits. This study uses observation techniques towards Secondary data obtained from annual financial reports and audited financial reports of manufacturing companies listed on the Indonesia Stock Exchange 2016-2018. The sample of this study were 59 manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique in this study using judgment sampling. Testing data with classical assumptions and using multiple regression analysis with SPSS version 24. Keyword: Effective Tax Rate, Size, Leverage, Profitability. References: Ambarukmi, Khusniyah Tri., Nur Diana (2017), Pengaruh Size, Leverage, Profitabilitas, Capital Intensity dan Activity Ratio Terhadap Effective Tax Rate (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di BEI Selama Periode 2011- 2015). Jurnal Ilmiah Riset Akuntansi, Vol.6 , p13–26. Ardyansah, Danis dan Zulaikha (2014), Pengaruh Size , Leverage , Profitability , Capital Intensity Ratio dan Komisaris Independen Terhadap Effective Tax Rate. Diponogoro Journal of Accounting, Vol.3, p1–9. Bursa Efek Indonesia, diakses 6 Desember 2020, idx.co.id. Batmomolin, Salestina. (2018). “Analisis Leverage , Firm Size , Intensitas Aset Tetap Dan Intensitas Persediaan Terhadap Tarif Pajak Efektif (Pada Perusahaan Kmia Terdaftar Di Bursa Efek Indonesia Tahun 2012-2017). Jurnal Ilmiah Buletin Ekonomi, Vol 22, p36-42. Daftar Perusahaan Manufaktur, diakses 6 Desember 2020, sahamok.com Ghozali, Imam. (2016). Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23. Semarang: Penerbit Universitas Diponegoro. Hery, (2015), Pengantar Akuntansi and Comprehensive Edition, Indonesia: Gramedia Widiasarana Indonesia. Imelia, Septi. (2015). Analisis Faktor Yang Mempengaruhi Manajemen Pajak Dengan Indikator Tarif Pajak Efektif (ETR) Pada Perusahaan Lq45 yang Terdaftar Dalam Bursa Efek Indonesia Tahun 2010-2012. Jom FEKON, Vol 2, p1-15. Kasmir (2018), Analisis Laporan Keuangan, Edisi Kesebelas, Depok : Penerbit PT RajaGrafindo Persada. Kurniasari, Erni., Listiawati. (2019). Profitabilitas Dan Leverage Dalam Mempengaruhi Effective Tax Rate. Jurnal Manajemen, Vol 9 p17-29. Kurniawan, Indra Suyoto. (2019). Analisis Faktor Yang Mempengaruhi Manajemen Pajak Dengan Indikator Pajak Efektif. Fakultas Ekonomi dan Bisnis Universitas Mulawarman, Samarinda 16(2), p213–221. Putri, Amanda Nur., Gunawan. (2017). Pengaruh Size , Profitability , Dan Liquidity Terhadap Effective Tax Rates ( ETR ) Bank Devisa Periode 2010 – 2014. Jurnal Keuangan dan Perbankan, Vol 14, No 1, p18-28. Putri, Citra Lestari., Lautania, Maya Febrianty. (2016). Pengaruh Capital Intensity Ratio, Inventory Intensity Ratio, Ownership Structure Dan Profitability Terhadap Effective Tax Rate (ETR) (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014). Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi (JIMEKA), Vol 1, No 1, p101-119. Putri, Khurin’in Kurnia. (2017). Pengaruh Corporate Governance, Ukuran Perusahaan, Rasio Hutang Dan Profitabilitas Terhadap Tarif Pajak Efektif. JOM Fekon, Vol 4, No 1, p1501–1515. Republik Indonesia (2007), Undang-Undang nomor 28 tahun 2007 Undang-Undang tentang Perubahan Ketiga Atas Undang-Undang Nomor 6 Tahun 1983 Tentang Ketentuan Umum dan Tata Cara Perpajak, Sekretariat Negara Republik Indonesia (2008), Undang-Undang nomor 36 tahun 2008 Undang-Undang tentang Perubahan Ketiga Atas Undang-Undang Nomor 7 Tahun 1983 Tentang Pajak Penghasilan, Sekretariat Negara Richardson, Grant., Lanis, Roman (2007) Determinants of the Variability in Corporate Effective Tax Rates and Tax Reform : Evidence from Australia, Journal of Accounting and Public Policy 26, p689–704. Rodriguez, Fernandez Elena., Arias, Martinez Antonio (2012), Size and Other Determinants of Corporate Effective Tax Rates in US Listed Companies, International Research Journal of Finance and Economics, No.9, p160-165 Susilowati, Yeye., Ratih Widyawati., dan Nuraini (2018). Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas, Capital Intensity Ratio Dan Komisaris Independen Terhadap Effective Tax Rate (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia pada Tahun 2014-2016). Prosiding SENDI_U, p796–804. Waluyo (2017), Perpajakan Indonesia, Edisi Keduabelas, Jakarta: Penerbit Salemba Empat. Wati, Putri., Sri Ruwanti, dan Fatahurrazak (2018). Pengaruh Chief Financial Officer Expert Power, Chief Financial Officer Political Power, Leverage, Profitability Dan Intensitas Persediaan Terhadap Tarif Pajak Efektif Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2016. Jurnal Ekonomi Fakultas Ekonomi Universitas Maritim Raja Ali Haji, p1–20.